2023
DOI: 10.1021/acs.macromol.3c01168
|View full text |Cite
|
Sign up to set email alerts
|

A β-Form Crystal Modification of Poly(glycolic acid): Formation, Stabilization, and β–α Transition

Deyu Niu,
Hai Wang,
Ye Ma
et al.

Abstract: Polymorphism is one of the fascinating characteristics of polymer crystallization. In this work, we report a new crystal modification of poly­(glycolic acid) (PGA), the β-form, to be distinguished from the already known α-form PGA crystal reported in 1968. The β-form with a relatively high amount (X β = 43%) is obtained during isothermal crystallization in a particular temperature domain, i.e., T c around 60 °C, after prestretching the amorphous samples. The orientation of PGA amorphous chains is expected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…However, as reported in the reference, a new crystal modification (β form) of PGA was discovered in our recent work by stretching the melt-quenched amorphous sample below the glass transition point. The X-ray diffraction pattern of the β form is very different from that of the α form.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, as reported in the reference, a new crystal modification (β form) of PGA was discovered in our recent work by stretching the melt-quenched amorphous sample below the glass transition point. The X-ray diffraction pattern of the β form is very different from that of the α form.…”
Section: Introductionsupporting
confidence: 68%
“…The β form is thermodynamically unstable compared to the α form. In fact, in the present study, the β-to-α phase-transition enthalpy (exothermic) observed in the DSC measurement was about −7.5 J/g for the PGA sample with the degree of crystallinity 0.45 . Since the molecular weight of one monomeric unit is 58 g/mol, the transition enthalpy of the pure crystal phase is estimated as Δ H = H α – H β = −7.5 J/g × 58 g/mol m.u./0.45 = −0.97 kJ/mol m.u.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…PGA exhibits great competitiveness in green packaging and agricultural films due to its excellent barrier properties. 6 The oxygen permeability of PGA is approximately 100 times lower than that of poly(ethylene terephthalate) (PET). Several studies have enhanced the barrier properties in various polymers such as PET and poly(butylene adipate-co-terephthalate) (PBAT) by incorporating PGA.…”
Section: Introductionmentioning
confidence: 99%
“…PGA exhibits great competitiveness in green packaging and agricultural films due to its excellent barrier properties . The oxygen permeability of PGA is approximately 100 times lower than that of poly­(ethylene terephthalate) (PET).…”
Section: Introductionmentioning
confidence: 99%